Study on the two-way corrugated aluminum honeycomb as a filler material in impact limiters for spent fuel transport casks. Issue 5 (4th May 2019) - Li, Zhongfang; Yang, Siyi; Xu, Haile; An, Yukun; Zhao, Ertuan
ABSTRACT: Impact limiters installed on nuclear spent fuel transport casks are used to absorb energy and limit overload during transport and accidents. The two-way corrugated aluminum honeycomb, a new kind of filler material, is designed based on the action mechanism of the impact limiter. Quasi-static compression tests are used to compare the properties of the honeycomb and the traditional filler material, paulownia wood. Experimental results indicated that the compressive and energy absorption properties of paulownia wood with axial wood grain and radial wood grain were very different. Also, the moisture content of paulownia wood led to a significant decrease in its properties. The two-way corrugated aluminum honeycomb, as a new porous material, showed better compression and energy absorption properties than paulownia wood in the x, y, and z directions. The peak stress ( σpe ), platform stress ( σpl ), and energy absorption capacity ( WEA ) were 2.10 times, 2.07 times, and 1.69 times higher than that of paulownia wood with axial wood grain. The two-way corrugated aluminum honeycomb is a filler material that has essential application value in impact limiters of spent fuel transport casks.